Individual Pro-Environmental Behavior: A Study On Employees In Indonesia's Banking Industry - Muhammad Zufar Aminullah; Dian Ekowati (Publikasi Indonesia, 2025)
Purpose – The study examines the relationship between green transformational leadership, green training and development, green performance management, green organizational culture, and green social capital in influencing pro-environmental behavior. It explores how perceived government pressure moderates the relationship between green organizational culture and pro-environmental behavior, while also investigating the mediating role of green organizational culture and green social capital in these relationships. Design/methodology/approach – Data were gathered from 210 employees in Indonesia banking industry through structured questionnaires using a five-point Likert scale. Structural Equation Modeling (SEM) with SmartPLS 3 was employed to test the proposed hypotheses. Findings – The results show that green transformational leadership, green performance management, and green social capital have a positive and significant impact on proenvironmental behavior. However, green training and development and green organizational culture do not have a significant direct effect. Perceived government pressure is found to positively and significantly moderate the relationship between green organizational culture and pro-environmental behavior. Practical Implications – This study offers practical guidance for organizations seeking to foster a pro-environmental behavior among employees. By strengthening green leadership approaches, practicing green human resource management, and responding to external influences, companies can effectively integrate sustainability into their daily operations and behavior, Fostering sustainable environmental responsibility and active participation from their employees. Social Implications – The study shows that green practices in muman resource management and green transformational leadership are essential in shaping pro-environmental behavior through organizational culture and social capital.